PENGARUH KOMISARIS INDEPENDEN, UKURAN PERUSAHAAN, DAN UMUR PERUSAHAAN TERHADAP PENGUNGKAPAN ISLAMIC SOCIAL REPORTING (ISR) - Astari Nur Irbah (2021)
This study is aimed to analyze the Independent Commissioner, Company Size, and Company Age variables can influenxe the Islamic Social Reporting Disclosure on listed companies in the Jakarta Islamic Index (JII). The independent variables used in this study are the Independent Commissioner variable which is measured using proportion of independent commissioner, Company Size is measured using natural logarithm of total assets, and Company Age is meausred using the time between the initial creation and the research time. And the ISR disclosure variable adopts measurement from the research of Othman dan Thani (2010). Multiple linear regression analysis is used as the method of this research with the population of companies listed on the Jakarta Islamic Index (JII) in 2017-2019 period. After selecting the sample using purposive sampling technique, 19 companies were obtained as samples in this study. The results of this study imply that Company Size affects ISR disclosure, while Independent Commissioner and Company Age do not affect ISR disclosure.